St. Vincent and the Grenadines : 2016 Article IV Consultation-Press Release; Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that St. Vincent and the Grenadines' recovery from the global financial crisis was hampered by a series of natural disasters, sluggish global demand, and slow implementation of key infrastructure projects. Economic activity appears to have recovered in 2015, led by strong tourism inflows and a rebound in construction. Inflation has trended down owing to falling food and fuel prices. The new airport, now foreseen for completion in 2016, is expected to sustain the near- and medium-term economic growth. Real GDP is projected to expand by 2.2 percent in 2016 and reach 3.1 percent over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet